One-Carbon Metabolism Links Nutrition Intake to Embryonic Development via Epigenetic Mechanisms - Si Wu; Jun Zhang; Feifei Li; Wei Du; Xin Zhou; Mian Wan; Yi Fan; Xin Xu; Xuedong Zhou; Liwei Zheng; Yachuan Zhou (Hindawi Limited, 2019)
Beyond energy production, nutrient metabolism plays a crucial role in stem cell lineage determination. Changes in metabolism based on nutrient availability and dietary habits impact stem cell identity. Evidence suggests a strong link between metabolism and epigenetic mechanisms occurring during embryonic development and later life of offspring. Metabolism regulates epigenetic mechanisms such as modifications of DNA, histones, and microRNAs. In turn, these epigenetic mechanisms regulate metabolic pathways to modify the metabolome. One-carbon metabolism (OCM) is a crucial metabolic process involving transfer of the methyl groups leading to regulation of multiple cellular activities. OCM cycles and its related micronutrients are ubiquitously present in stem cells and feed into the epigenetic mechanisms. In this review, we briefly introduce the OCM process and involved micronutrients and discuss OCM-associated epigenetic modifications, including DNA methylation, histone modification, and microRNAs. We further consider the underlying OCM-mediated link between nutrition and epigenetic modifications in embryonic development.